DESIGN OF ANDROID-BASED ZAKAT INFORMATION SYSTEM APPLICATION AT BABUL FIRDAUS MOSQUE - Kasmawati; Mustamin, Mustamin; Hasrul, Hasrul (Journal of Electrical Engineering and Informatics, 2025)
This research aims to make it easier for the community to do zakat and improve the data collection system. The method used is Research and Development (R&D) with a prototype development model, as well as data collection techniques through interviews, observations, and questionnaires. The result of this research is an Android-based zakat information system application intended for admins and people who want to do zakat at the Babul Firdaus Mosque. This application is tested using the ISO 25010 standard with four main aspects: functional suitability, portability, usability, and performance efficiency. Functional suitability testing by the validator lecturer shows that this application is "Feasible" to use. Portability testing is carried out by observing the output results on different versions of Android. Usability was tested by users and mosque administrators with a result of "Very Good". Performance efficiency is measured using the Android Studio profiler, showing CPU usage of less than 50%, 250 MB memory, and network activity of 64 Kb/s. This application has been accepted by users and is effectively used as a medium to make it easier for people to do zakat.